Wykorzystanie funkcji dyskryminacyjnej jako narzędzia wspomagającego wybór spółek do portfela papierów wartościowych - Gierałtowska, Urszula (Using Discriminant Function as An Instrument of Portfolio Selection in the Capital Market, 2005)
In the article the author carried out the usage of discriminant function with a agglomerative measure as a criterion of discrimination in order to evaluate economic and financial condition of a company. The companies at the Warsaw Stock Exchange were classified on the basis of economic and financial measures in the years 2001-2003. The results of the classification were acceptable and they were used to predict to which of the two groups a company will belong. The results of this evaluation and analysis were compared with the results of nonclassical methods. The structural assumptions of the function were not fulfilled, but the function was a good identifier all the same.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 407-415